SISTEM LAMPU JALAN OTOMATIS BERBASIS SENSOR LIGHT DEPENDENT RESISTOR - Viki Priadi; Muhammad Arifin; Afdeli Hasni; Geulis Alya Byrin; Ineke Putri; Risma Dani; Yuris Ramadhona; Achmad Aflah Jamazy (Teknik Elektro Polsri, 2026)
Street lights play a crucial role in supporting environmental safety and security. However, conventional street lighting systems remain inefficient due to their lack of automation. This research aims to design an automated street light security system based on a Light Dependent Resistor (LDR) sensor. The LDR sensor is used to detect ambient light intensity and serves as the basis for automatically controlling the lights, turning them on when it's dark and off when it's bright. Test results show that the system works well and is responsive to changes in light, improving energy efficiency and reducing reliance on manual operation